Those challenging first years (Journal of Parents and Teachers, 2023)
The article exposes the main problems that the kids have in their first twelve years. It divides them in four stages and discusses the most common conflicts adding the reasons from these problems and some tips for the families.
Keywords: conflicts; education; childhood